Grey zone lymphoma with features intermediate between diffuse large B‐cell lymphoma and classical Hodgkin lymphoma: a clinicopathological study of 14 Epstein–Barr virus‐positive cases. Issue 4 (16th December 2016) - Elsayed, Ahmed A; Satou, Akira; Eladl, Ahmed E; Kato, Seiichi; Nakamura, Shigeo; Asano, Naoko
Abstract : Aims: To investigate the clinicopathological features of Epstein–Barr virus (EBV)‐positive grey zone lymphoma (GZL) with features intermediate between diffuse large B‐cell lymphoma (DLBCL) and classical Hodgkin lymphoma (CHL). Methods and results: We investigated the clinicopathological features of 14 cases of EBV‐positive GZL in Japan. The control group included 173 cases of EBV‐positive CHL and 64 cases of EBV‐positive DLBCL of the elderly (polymorphous type). The patients were 10 men and four women with a median age of 62 years. Twelve patients (86%) had advanced clinical stage, 11 (79%) had B‐symptoms, eight (57%) had mediastinal disease, 10 (71%) had elevated serum lactate dehydrogenase (LDH) levels, and five (36%) had thrombocytopenia. All cases had CHL‐like morphology but strongly expressed at least one B‐cell marker. The neoplastic cells were Hodgkin and Reed–Sternberg‐like cells, but with a large number of mononuclear variants. EBV‐positive GZL patients were more significantly more likely than EBV‐positive CHL patients to have advanced clinical stage ( P = 0.023), presence of B‐symptoms ( P = 0.011), elevated serum LDH levels ( P = 0.047), thrombocytopenia ( P = 0.042), and mediastinal involvement ( P = 0.023). The progression‐free survival (PFS) of EBV‐positive GZL patients was significantly poorer than that of EBV‐positive CHL patients ( P = 0.043) but no difference from EBV‐positive DLBCL patients was observed ( P = 0.367). Conclusions: EBV‐positive GZL patients have significantly worse PFS than EBV‐positive CHL patients, and are significantly more likely to have adverse clinical parameters such as advanced clinical stage, presence of B‐symptoms, and thrombocytopenia. Further studies are needed to better characterize this entity, which may require the development of innovative therapeutic strategies.